The Analysis of the Effect and Reduction of Carrier Frequency Offset in Orthogonal Frequency Division Multiplexing (OFDM) Multiple Input Multiple Output (MIMO) - Sucipto, Willy; Pramaita, I Nyoman; Wirastuti, NMAE Dewi (Majalah Ilmiah Teknologi Elektro, 2020)
Abstract— The development of cellular telecommunication provides users to experience fast and stable transmission. This standard of transmission is proportional to the needs of the devices and systems used. We are currently in the fourth generation (4G) of cellular technology. The key technologies used in 4G are Orthogonal Frequency Division Multiplexing (OFDM) which uses the concept of orthogonality for bandwidth efficiency and Multiple Input Multiple Output (MIMO) which uses the concept of diversity to improve performance. But in implementation this system will have problems with the transmission channel. The problem that occurs is signal attenuation due to Carrier Frequency Offset (CFO). This CFO will cause the orthogonal character built from the OFDM system to experience a decline in performance. The decline in performance is due to the occurrence of Intercarrier Interference (ICI). To overcome this problem, the method used in this simulation are Improved Sinc Power Pulse (ISP) and Rectangular Pulse (REC). The results showed that ISP had a relatively better BER value than REC and without using the pulse shaping method. The minimum BER value obtained from the simulation is ISP with a value of 0.0001 while REC produces a value of 0.0006 and without pulse shaping produces a BER value of 0.0038.